MYCOBACTERIOSIS: A REVIEW OF EVIDENCE-BASED CLINICAL MANIFESTATIONS AMONG HUMANS - F.S. PETROVA; I.V. PETROV; T.KH. AMIROVA; L.V. PETROVA (Avicenna Tajik State Medical University, 2020)
The review presents data on proven clinical manifestations of the disease caused by non-tuberculosis mycobacteria. It was determined that pulmonary mycobacteriosis is one of the most common clinical forms of this mycobacterial infection, which is characterized by intoxication and respiratory syndromes. Dust in the air of the working area, as a professional factor, contributes to the emergence of pneumoconiosis and silicosis associated with mycobacteria. It is proved that M. avium has the ability to damage the intestinal mucosa, causing bacteremia and secondary damage to the bone marrow and spleen. The researchers point to the fact that non-tuberculosis mycobacteria can cause lymphadenopathy with lesions of the intraabdominal and cervical lymph nodes. Also, there is the possibility of mycobacteriosis of the skin. It is proved that mycobacterial infection contributes to the development of calcification of mitral, aortic valves and coronary arteries. It was determined that in the etiology of acute pancreatitis mycobacteriosis also plays definite role.